The contextual effect of completion on the effectiveness of performance feedback - Nicole Nikiforow; Sebastian Wagener (Journal of Business Economics, 2020)
This study investigates the varying effect of performance feedback on performance, depending on the task context. Specifically, we analyze the state of completion (of a product or process) as an essential dimension of the task context. Using a laboratory experiment, we predict and find that performance is lower under completion than under non-completion. Further, we predict and find that the effect of performance feedback on performance differs depending on the state of completion. Specifically, performance feedback increases performance under completion. However, on average, performance feedback is ineffective for non-completion. Our results extend research on the interplay between feedback and contextual factors within firms by providing initial evidence of the impact of the state of completion. In addition, our study has important implications for performance feedback design choices.
Keywords: C91; M11; M41; M54; 650; Completion; Feedback; IKEA effect; Performance information; Task context